DIALEKTIKA DAN REFLEKSI KRITIS REALITAS “SUSTAINABILITY” DALAM PRAKTIK SUSTAINABILITY REPORTING: SEBUAH NARASI HABERMASIAN - Dewi, I Gusti Ayu Agung Omika (UI Scholars Hub, 2010)
This study aims at achieving the understanding about sustainability reality which is reflected in the practice of sustainability reporting on State-Owned Enterprise of mine sector which is go public in Indonesian Stock Exchange. The paradigm of this study differs from the previous accounting researches which is used legitimacy theory as an analysis instrument. The analysis method which is used in this study is critical dialectic method on document in order to reflect sustainability reality in the practice of sustainability reporting according to Habermas perspective frame which known as: (1) Pseudo Sustainability; (2) Obligatory Sustainability; and (3) Humanism Sustainability. The result shows that sustainability reality known as obligatory sustainability and humanism sustainability. The sustainability reality which known as obligatory sustainability is accordance to legitimacy theory which is density of capitalistic values. Whereas, sustainability reality which known as humanism sustainability is accordance to Habermas perspectives, which balanced the role of human being as an individual and as social human being all at once, as the basis of humanism values development.